Participation to the People! Locating the Popular in Rimini Protokoll’s Home Visit Europe - Berg, Ine Therese (Nordic Theatre Studies, 2018)
Home Visit Europe by Rimini Protokoll is a performance without performers, only an audience taking part in a game in a private home. As such, it is one example of the participatory strategies that currently have a strong presence in contemporary theatre practices changing how we, as audience, engage with theatre. It is emblematic then that ‘participation’ is an emergent concept in theatre and performance studies with a rapidly growing body of work on the topic. This article sets out to explore how the idiom of the popular can shed light on some of the central issues in the discourse on participation: that is to say, the relationship between the artist and the audience, authorship, and the relationship between the aesthetic and the social dimension of participatory work. I will be using Home Visit Europe in the context of Bergen International Festival of 2015 as a case study, drawing on an audience research approach combined with a critical reading of the work. The conceptually stringent and tightly ordered dramaturgy of Home Visit Europe, where the audience take turns responding to a set of questions and tasks, demonstrates how problematic the concept of participation can be to describe theatre practices, as the term risks overstating the influence that the audience have over the aesthetic product. In this sense, contemporary participatory strategies resemble popular theatre’s conflict between established aesthetics, critical standards and popular grounding. A resemblance that brings the paper right to the core of the discourse on participation, which concerns the ideological ramifications of the ‘participatory turn’.